A Randomized Trial of Robot-Assisted Laparoscopic Radical Cystectomy - Bochner, Bernard H; Sjoberg, Daniel D; Laudone, Vincent P (The New England journal of medicine, 2014)
In a single-center, randomized trial comparing robot-assisted laparoscopic radical cystectomy with open surgery, there was no significant between-group difference in the rates of perioperative complications of grade 2 to 5. To the Editor: Radical cystectomy is the standard management of nonmetastatic, invasive bladder cancer. However, this treatment is associated with clinically significant perioperative complications and prolonged recovery time among patients with this disease, who are typically older and often have a history of smoking and coexisting conditions. 1 , 2 Retrospective studies indicate that robot-assisted laparoscopic surgery is associated with a reduced risk of complications and shorter hospital stay, as compared with open surgery, 3 but data are lacking from randomized trials. We report the results of a randomized, controlled trial (ClinicalTrials.gov number, NCT01076387) designed to assess whether robot-assisted laparoscopic radical cystectomy would . . .